Widespread exposure of Noachian phyllosilicates in the Margaritifer region of Mars: Implications for paleohydrology and astrobiological detection. Issue 3 (11th March 2017) - Thomas, Rebecca J.; Hynek, Brian M.; Osterloo, Mikki M.; Kierein‐Young, Kathryn S.
Abstract: The best locations at which to detect evidence for early life on Mars are in materials formed in near‐surface aqueous environments, particularly where this resulted in the deposition of minerals such as clays that are favorable to preservation of organics. The geological history of the Margaritifer region has resulted in exceptional potential to preserve such deposits and to render them discoverable. Due to its topographic setting at the interface between highlands and lowlands, Margaritifer was a major sink for water and sediments in the early, Noachian, period, potentially creating environments that were habitable and conducive to clay formation. Subsequently, during the Late Hesperian to Amazonian, the ancient surface was extensively disrupted in association with the formation of multiple chaos regions. This activity had the potential to expose any astrobiological evidence from the earlier period. We used orbital image, spectral and topographic data to investigate the extent and means of exposure of Noachian clay‐bearing deposits across the region. We find that they are indeed exposed over a very wide area in Margaritifer and that their mineralogy is most consistent with clay formation in a low‐energy near‐neutral pH groundwater environment. We additionally find that evidence for subsequent acidic groundwater activity is absent, indicating that biosignature preservation in these units is favored, perhaps to a greater degree than for similar deposits in the surrounding region. Further, due to the intense Hesperian‐Amazonian geologic activity here, early clay‐bearing units are exposed to a greater degree than achievable in regions with more localized erosive mechanisms. Key Points: Potentially biosignature‐bearing Noachian sediments are exposed over a large area in the Margaritifer region The setting and mineralogy of many clay‐bearing units suggest in situ formation in stagnant, near‐neutral pH conditions Exposure results from intense Hesperian‐Amazonian geologic activity, giving the region unusually high biosignature detection potential